Conceptual and methodological challenges to measuring political commitment to respond to HIV - Fox, Ashley M.; Bärnighausen, Till (Journal of the International AIDS Society, 2011)
Background: Researchers have long recognized the importance of a central government’s political “commitment” in order to mount an effective response to HIV. The concept of political commitment remains ill-defined, however, and little guidance has been given on how to measure this construct and its relationship with HIV-related outcomes. Several countries have experienced declines in HIV infection rates, but conceptual difficulties arise in linking these declines to political commitment as opposed to underlying social and behavioural factors. Methods:This paper first presents a critical review of the literature on existing efforts to conceptualize and measure political commitment to respond to HIV and the linkages between political commitment and HIV-related outcomes. Based on the elements identified in this review, the paper then develops and presents a framework to assist researchers in making choices about how to assess a government's level of political commitment to respond to HIV and how to link political commitment to HIV-related outcomes Results: The review of existing studies identifies three omponents of commitment (expressed, institutional and budgetary commitment) as different dimensions along which commitment can be measured. The review also identifies normative and ideological aspects of commitment and a set of variables that mediate and moderate political commitment that need to be accounted for in order to draw valid inferences about the relationship between political commitment and HIV-related outcomes. The framework summarizes a set of steps that researchers can follow in order to assess a government's level of commitment to respond to HIV and suggests ways to apply the framework to country cases. Conclusions: Whereas existing studies have adopted a limited and often ambiguous conception of political commitment, we argue that conceiving of political commitment along a greater number of dimensions will allow researchers to draw a more complete picture of political commitment to respond to HIV that avoids making invalid inferences about the relationship between political commitment and HIV outcomes.